USING CRITICAL READING STRATEGIES; ONE WAY FOR ASSESSING STUDENTS’ READING COMPREHENSION - Eka Sustri Harida (Universitas Negeri Padang, 2016)
Assessment is the evaluation for the students’ ability in one material or one subject of learning in order to know how far the students understand the material are, and it needs an authentic one to get the best result of the students’ learning. Many assessment have been done in assessing students’ reading comprehension, meanwhile not all assessment is appropriate to the students’ need. Moreover, in assessing students’ reading comprehension, an authentic assessment can be in the real world or the real context for their living and their environment. An Authentic Task is an assignment given to students designed to assess their ability to apply standard-driven knowledge and skills to real-world challenges. One way to assess students’ reading comprehension can be done by using Critical Reading Strategies. It is known that the strategy help the students in comprehending the contents of the text well. By applying the strategies, the students will be more comprehend about the text. It is realized that it is difficult for the students to use it, meanwhile it is proved that it makes the students understand the text well. Thus, it can be concluded that the students’ reading comprehension can be evaluated by using Critical Reading Strategies, and it is proved that it has good result.